Contemporary architecture in seismic zones, concepts and realizations - Enis JAKUPI; Erda BESIMI (Micro, Macro & Mezzo Geoinformation, 2020)
With the rapid development of society and the demand for a better and more modern life, there is a need for the development of civil engineering in general, and of earthquakes. Recently, we are witnessed by many natural disasters occurring in the world, leaving huge footprints, taking a large toll on human lives and causing extensive material damage. The main problems remain without clear and precise answers now. Which arise during the impacts of dynamic loads, and the origin of those loads can be from: earthquakes, winds, explosions, working with cars, etc. Earthquakes are still one of the greatest nature threats which is causing to mankind. Although earthquakes cannot be prevented, modern science and engineering have provided the means and tools that if they will be used properly can significantly reduce the impact of powerful earthquakes.